2017
DOI: 10.1007/s11010-017-3218-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a suppresses invasion and metastatic in esophageal squamous cell carcinoma by regulating CD44

Abstract: In human esophageal squamous cell carcinoma (ESCC), miR-34a was downregulated and could inhibit in vitro cell proliferation and migration. However, the underlying mechanism was not clear yet. The expression levels of mRNA and protein were detected by quantitative real-time PCR or western blotting, respectively. MiR-34a was knocked down or overexpressed and transfected into human ESCC cell lines ECA109 and TE-13, respectively. Cell migration and wound healing assays were used to examine the effect on migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Although the effects of miR-34a (30,31) as well as FOXM1 (32,33) have already been investigated in ESCC, and miR-34a could regulate the progression of hepatocellular carcinoma via targeting FOXM1 (13), it has not been investigated whether miR-34a could regulate the progression of ESCC via targeting FOXM1. Consistent with these studies, we demonstrated the upregulation of FOXM1 in ESCC patients compared with paired cancer-adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of miR-34a (30,31) as well as FOXM1 (32,33) have already been investigated in ESCC, and miR-34a could regulate the progression of hepatocellular carcinoma via targeting FOXM1 (13), it has not been investigated whether miR-34a could regulate the progression of ESCC via targeting FOXM1. Consistent with these studies, we demonstrated the upregulation of FOXM1 in ESCC patients compared with paired cancer-adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The 3′ untranslated region of CD44, acting as a competing endogenous RNA to microRNA-34a, boosts the sensitivity of liver CSCs to natural kill cells-mediated cytotoxicity via regulating UL16 binding protein 2 [26]. In addition, CD44 also exerts significant effects on caner invasion and metastasis of various tumor types [27], such as lung adenocarcinoma [18], breast cancer [28][29][30], neuroblastoma [31], gastric cancer [32], esophageal squamous cell carcinoma (ESCC) [33], colorectal cancer [34][35][36][37], prostate cancer [38], nasopharyngeal carcinoma [39], endometrial cancer [40], clear cell renal cell (RCC) carcinoma [41], pancreatic cancer [42], meningioma [43] and ovarian cancer [44]. As has been reported, the intracellular domain (ICD) of CD44 interacting with RUNX2 to form a co-transcription factor drives the migration of prostate cancer cell line PC3 through upregulating the levels of metastasis-related genes, such as matrix metalloproteinase 9 (MMP9) and osteopontin [38].…”
Section: Open Accessmentioning
confidence: 99%
“…Studies have reported that miR-34a functions as an EMT inhibitor as it reduces the intensity of ESCC progression by binding to phospholipase C elipson 1 (PLCE1) [61]. In another study on ESCC progression, overexpression of miR-34a was found to decrease the number of metastatic nodules in the liver via directly targeting CD44 [110]. At present, various miRNAs have been found to regulate EMT or tumor metastasis of ESCC.…”
Section: Non-coding Rnas and Emt And Metastasis In Esccmentioning
confidence: 99%
“…Many such studies have been published so far, which reveal miRNAs as tumor suppressors or oncogenes (Table 1). For example, miR-146a, miR-133b, miR-106b-3p, miR-219-5p, miR-206, miR-384, miR-455-5p, miR-128, miR-145-3p/5p, miR-10b-3p, miR-874-3p, miR-10a, miR-365, miR-301a, miR-6775-3p, miR-139-5p, miR-516b, miR-449a-5p, miR-125b, miR-433-3p, miR-370, miR-133b, miR-30a-3p/5p, miR-34a, miR-196a, and miR-125b-5p have been shown to act as tumor suppressors by inhibiting ESCC cell proliferation, promoting apoptosis by directly targeting oncogenes, or antagonizing pro-cancer signaling pathways [29,33,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][60][61][62][63]110,133]. In contrast, pro-oncogenes such as miR-141, miR-21, miR-10b-3p, miR-424, miR-675-3p, miR-543, miR-135, miR-23b-3p, miR-502, miR-21-5p, and miR-548k have been reported to play contrasting roles in promoting cell proliferation or suppressing apoptosis in ESCC [47,[64][65][66][67][68][69][70][71][72][73].…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%